CIRCULATION IN THE BLOOD COMPOSITION OF PREECLAMPSIA PROGNOSTIC BIOMARKERS (International Journal of Scientific Pediatrics, 2023)
The article, based on an analysis of modern literature, discusses the etiology and pathogenesis of the most dangerous complication of pregnancy - preeclampsia and the possibilities of predicting this pathology. The relevance of the problem associated with preeclampsia is due to its leading third position in the structure of maternal mortality, as well as serious long-term cardiometabolic disorders in women who have suffered this complication, which significantly reduce their quality of life. Based on the results of studying the pathogenesis of preeclampsia, new biomarkers (substances used as indicators of a biological state) were identified; this concept is used to characterize markers suitable for predicting a biological condition, such as preeclampsia, for early detection and prevention of this pathology.
Keywords: preeclampsia; biomarkers; prognosis; prevention